PEMBUATAN PERANGKAT LUNAK SIMULASI HIDROGRAF INFLOW WADUK WONOGIRI PERIODE BANJIR - , ANANTRI SULISTYOWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wonogiri Reservoir is one of flood control building in the upper stream of Bengawan Solo River. Spillway gate operation during flood will perform well if it is supported by an integrated information system - inflow flood hydrograph estimation, reservoir flood routing, and impact of operation to the downstream of reservoir. In this study, a software for flood forecasting simulation was developed to estimate inflow flood hydrograph of Wonogiri Reservoir during flood period based on some studies of hydrologic model and realtime monitoring information obtained from some observation stations. This software was developed by using Microsoft Visual Studio 2010. The calculation process of this software is using rainfall-runoff simulation model which consist of baseflow model, transform method, and losses model. Input realtime data were obtained from 5 ARR and 4 AWLR stations in 10 watershedâs Wonogiri Reservoir managed by Perum Jasa Tirta I Bengawan Solo. In this research, the software was simulated by using observed data in 25 January 2014. Based on the simulation, the inflow hydrograph obtained from this software is equal to the result of manual calculation using Microsoft Excel. The softwareâs output will consist of inflow hydrograph to Sediment Storage Reservoir and Main Reservoir based on the latest condition of Wonogiri Reservoir in which this reservoir will have closure dike and new spillway gate. Inflow hydrographâs output during flood period can be used as an input to the reservoir flood routing. Therefore, the decision making process in the spillway gate operation for flood control in the upper stream of Bengawan Solo River will be effective and more accurate.